VALIDATION OF A SCALE FOR MEASURING PRECAUTIONS FOR SAFE USE OF ATM - George, Ajimon; George, Ajay (International Journal of Psychosocial Rehabilitation, 2020)
ATM fraud is a big threat and it requires a coordinated and cooperative action on the part of the bank, customers and the law enforcement machinery. It not only causes financial loss to banks but also undermine customers' confidence in the use of ATMs. The specific objectives of the study are (a) to develop and validate a scale for measuring the precautions taken by ATM users for the safe use of ATM and (b) to examine the adequacy or otherwise of the precautions taken by ATM users. The study is empirical in nature and survey method has been employed for collecting data from 342 respondents. The response was collected using a structured questionnaire which was pilot tested with 25 respondents who are using ATM. Non-Probability convenience sampling technique was used to identify the respondents. Seventeen statements were used to elicit precautions taken by ATM users for the safe use of ATM. These are the statements that describe the practices ATM users should follow while using ATM’s. The reliability of the measures is assessed by examining the Cronbach’s Alpha Coefficient. Exploratory Factor Analysis is used in the current study to explore six underlying dimensions of the measured items and each dimension were suitably labeled based on the characteristics of the items converged in each dimension. These six dimensions are precautions related to PIN, precautions related to Machine, Precautions related to Card, Precautions related to Cash, Precautions related to bank accounts and precautions related to transactions. These dimensions were further validated through confirmatory factor analysis. The findings have managerial implications for banks, as they will help them to take necessary steps to safeguard their customers against the risks associated with the use of ATM. The mean of percentage score of all the constructs were found to be above 80 percent except precautions related to Machine which is 72.4 per cent. This indicates that ATM users take fairly enough precautions while using ATM and found that comparatively highest precautions are taken on transactions dimension and lowest precautions related to machine. If banks can take initiative in creating awareness among their users to take more required precautions, it will instill more confidence among ATM users so that they can do banking transactions without the fear of risk and fraud. The most important contribution of this study to the existing literature is the development and validation of a scale for measuring the precautions for safe use of ATM.